Marine Borer Resistance of Resak Wood (Vatica sp.): Assessing Durability Across Different Immersion Depths - Hikma Yanti; Muhammad Riski; Muhammad Dirhamsyah; Ahmad Yani (Green Insight Solutions, 2025)
Wood submerged in brackish and marine environments is highly susceptible to degradation by marine borers, which can compromise its structural integrity over time. Resak wood (Vatica sp.), widely used in boat construction, is frequently exposed to seawater, making it vulnerable to such bio-deterioration. This study aimed to assess the intensity of marine borer attacks on resak wood at different immersion depths (5 cm, 25 cm, and 50 cm) over three months in the estuary of Mempawah River, Mempawah Regency. Test samples (2 cm × 5 cm × 30 cm) were deployed, and data were analyzed using a Completely Randomized Design (CRD) with five replications, totaling 15 samples. The results revealed that resak wood exhibits high natural durability and is classified as durability class I, indicating strong resistance to marine borer infestations. The recorded weight loss percentages were 1.48% at 5 cm depth, 1.81% at 25 cm depth, and 2.69% at 50 cm depth, with statistical analysis confirming a significant effect of immersion depth on weight loss. This suggests that while resak wood is highly resistant, degradation intensifies with increasing submersion depth. Four marine borer species were identified in the estuarine waters of the Mempawah River: Limnoria sp., Balanus sp., Nereis sp., and Teredo sp. Their presence highlights the potential threat to submerged wooden structures in the region. Despite its durability, prolonged exposure and greater immersion depth may gradually reduce the structural performance of resak wood. Further long-term studies are recommended to evaluate its resistance under diverse environmental conditions and to explore protective treatments that could enhance its durability in marine applications.